Ursodeoxycholic acid but not tauroursodeoxycholic acid inhibits proliferation and differentiation of human subcutaneous adipocytes - Mališová, Lucia; Kováčová, Zuzana; Koc, Michal; Kračmerová, Jana; Stich, Vladimír; Rossmeislová, Lenka (PloS one, 2013)
Stress of endoplasmic reticulum (ERS) is one of the molecular triggers of adipocyte dysfunction and chronic low inflammation accompanying obesity. ERS can be alleviated by chemical chaperones from the family of bile acids (BAs). Thus, two BAs currently used to treat cholestasis, ursodeoxycholic and tauroursodeoxycholic acid (UDCA and TUDCA), could potentially lessen adverse metabolic effects of obesity. Nevertheless, BAs effects on human adipose cells are mostly unknown. They could regulate gene expression through pathways different from their chaperone function, namely through activation of farnesoid X receptor (FXR) and TGR5, G-coupled receptor. Therefore, this study aimed to analyze effects of UDCA and TUDCA on human preadipocytes and differentiated adipocytes derived from paired samples of two distinct subcutaneous adipose tissue depots, abdominal and gluteal. While TUDCA did not alter proliferation of cells from either depot, UDCA exerted strong anti-proliferative effect. In differentiated adipocytes, acute exposition to neither TUDCA nor UDCA was able to reduce effect of ERS stressor tunicamycin. However, exposure of cells to UDCA during whole differentiation process decreased expression of ERS markers. At the same time however, UDCA profoundly inhibited adipogenic conversion of cells. UDCA abolished expression of PPARγ and lipogenic enzymes already in the early phases of adipogenesis. This anti-adipogenic effect of UDCA was not dependent on FXR or TGR5 activation, but could be related to ability of UDCA to sustain the activation of ERK1/2 previously linked with PPARγ inactivation. Finally, neither BAs did lower expression of chemokines inducible by TLR4 pathway, when UDCA enhanced their expression in gluteal adipocytes. Therefore while TUDCA has neutral effect on human preadipocytes and adipocytes, the therapeutic use of UDCA different from treating cholestatic diseases should be considered with caution because UDCA alters functions of human adipose cells.
Keywords: Gene Expression Regulation; kyselina ursodeoxycholová; Enzyme Activation; adipogeneze; Taurochenodeoxycholic Acid; Cell Proliferation; cytokiny; buněčná diferenciace; Mitogen-Activated Protein Kinase 3; Adipocytes; kyselina taurochenodeoxycholová; podkožní tuk; stres endoplazmatického retikula; tukové buňky; lidé; ženské pohlaví; Adipogenesis; Ursodeoxycholic Acid; Humans; Subcutaneous Fat; regulace genové exprese; mitogenem aktivovaná proteinkinasa 3; aktivace enzymů; proliferace buněk; Cytokines; mitogenem aktivovaná proteinkinasa 1; Endoplasmic Reticulum Stress; Female; Mitogen-Activated Protein Kinase 1; Cell Differentiation